2007
DOI: 10.1002/jcp.21294
|View full text |Cite
|
Sign up to set email alerts
|

Adrenomedullin is anti‐apoptotic in osteoblasts through CGRP1 receptors and MEK‐ERK pathway

Abstract: Adrenomedullin (ADM) has been shown to mediate multifunctional responses in cell culture and animal system such as regulation of growth and apoptosis. ADM stimulates the proliferation of osteoblasts in vitro and promotes bone growth in vivo. The ability of ADM to influence osteoblastic cell number through inhibition of apoptosis has not yet been studied. To address this question we have investigated its effect on the apoptosis of serum-deprived osteoblastic cells using mouse MC3T3-E1 cells which express both A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
45
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 45 publications
(65 reference statements)
4
45
0
Order By: Relevance
“…The selective inhibitor of MAPK kinase (MEK), PD98059, also eliminates the protective effect of ADM on apoptosis and prevents ADM activation of ERK1/2. These data show that ADM acts as a survival factor in osteoblastic cells via a CGRP1 receptor-MEK-ERK pathway, which provides further understanding on the physiological function of ADM in osteoblasts (47).…”
Section: Discussionmentioning
confidence: 99%
“…The selective inhibitor of MAPK kinase (MEK), PD98059, also eliminates the protective effect of ADM on apoptosis and prevents ADM activation of ERK1/2. These data show that ADM acts as a survival factor in osteoblastic cells via a CGRP1 receptor-MEK-ERK pathway, which provides further understanding on the physiological function of ADM in osteoblasts (47).…”
Section: Discussionmentioning
confidence: 99%
“…However, though, cAMP-PKA pathways are coupled to ADM receptors in various types of cells, in osteoblastic cells, changes in cAMP observed by Hamada et al [2002] in the proliferative effect of ADM, had previously been reported to be limited by Grey et al [1999], while for this author, MAPK appeared to be the major pathway mediating the mitogenic effect of ADM. PI3K/Akt signaling has been observed to be activated in some cell types, as in particular, endothelial cells and vascular smooth muscle cells [Iwasaki et al, 2001;Kim et al, 2003], but nothing has been reported about this signaling pathway in osteoblasts. Moreover, as the action of ADM can also be mediated through the CGRP receptor, as has been reported for its mitogenic and anti-apoptotic effects in osteoblasts [Cornish et al, 2003;Uzan et al, 2008], ADM could potentially activate the same signaling pathways as CGRP in osteoblasts. In this sense, it should be noted that it was recently observed [Mrak et al, 2010] that in osteoblasts, CGRP is able to modify the glycogen synthase kinase 3beta (GSK3b) protein and Wnt signaling, which both play an important role in the control of apoptosis [Bodine, 2008].…”
mentioning
confidence: 92%
“…ADM has been reported to exert potent bone-stimulatory actions in vivo and to stimulate osteoblast proliferation in vitro [Cornish et al, 1997;Naot et al, 2001;Hamada et al, 2002]. In a previous study, we reported that in addition to its proliferative effect, the action of ADM in osteoblastic cells may also imply the inhibition of apoptosis [Uzan et al, 2008]. It was effectively observed that ADM treatment inhibited apoptosis induced by the withdrawal of growth factors in osteoblastic cells.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…This peptide is released in circulation where it can exert hypotensive effects, acting on vasodilatation and increasing diuresis and Na C secretion in urine (Nishikimi 2007). It has also been shown that AM possesses a local proliferative and antiapoptotic action on several cell types, and is implicated in tumoral neoangiogenesis (Ishikawa et al 2003, Uzan et al 2008. The peptide AM acts through ADMR, RDC1, and calcitonin receptor-like (CRLR) E Thouë nnon, A Pierre et al: Trophic in pheochromocytoma www.endocrinology-journals.org receptors.…”
Section: Introductionmentioning
confidence: 99%